Pelatihan Kewajiban Pencatatan dan Pembukuan Bagi Wajib Pajak UMKM di Kecamatan Grogol Petamburan - Febrianti, Meiriska; Yohanes, Yohanes (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are types of businesses that are widely operated by individuals, households, and small enterprises. To fulfill their tax obligations, MSME taxpayers need to understand the principles of recording and bookkeeping, as these form the basis for calculating income tax liabilities. Trisakti School of Management's Center for Community Research and Development (P3M) collaborates with the Jakarta Grogol Petamburan Tax Office to provide guidance on how to maintain proper bookkeeping and recording for MSME taxpayers. This training event is conducted in partnership with the Kantor Kecamatan Grogol Petamburan, Jackpreneur, and Baqoel. The objective of this community service activity is to provide an understanding of how to maintain proper recording and bookkeeping for MSME taxpayers and how to calculate taxes using these records and books. The training method involves delivering materials through lectures, providing examples of recording and bookkeeping cases, and conducting tax calculations using the recorded data. The expected outcomes of this training are that participants will grasp their obligations when they possess a Tax Identification Number (NPWP) and will register their businesses to obtain an NPWP for those who do not have one. The ultimate target is to increase the number of MSME taxpayers who have an NPWP, make tax payments, and submit tax reports, thereby improving the compliance of MSME taxpayers.